From Margin to Centre: A Study of Ennoblement in Shobha De’s Socialite Evenings - Ramesh, T.S; Vanitha, R. (Crossing the Border: International Journal of Interdisciplinary Studies, 2017)
The protagonists of Shobha De do not want to be docile, weak and dependant women. They want to be powerful and ready to revolt against unfair treatment and are not for compromise. They always want to show self-confidence in abundance. Boldly, they are ready to challenge hinders so that they attain their desired goal. They tend to be aggressive always, which helps them to shatter the male ego and male hierarchy. In order to be precise, they are not doormats. They raise their voice strong against patriarchal culture and marginalization of women. Thus, this paper aims to prove that how women in India tend to be transformed from margin to centre. It also aims to prove the fact that they want to be liberated physically and mentally and long for an independent identity by being aware of the choices open to them. Crossing the Border: International Journal of Interdisciplinary Studies Vol.5(1) 2017: 51-60